Estimación de la longitud y el peso del pejerrey lagunero Odontesthes nigricans (Atherinopsidae) a partir de medidas morfométricas de los huesos craneales y de la cintura escapular - Navoa, Ximena (2024)
In the present work, regression equations were generated to estimate wet weight from total length and also to estimate wet weight and total length from skull and pectoral girdle bones length of Odontesthes nigricans. All regressions were statistically significant. No significant differences were found in the wet weight-total length relationship between males and females, showing a positive allometric growth between wet weight and total length. The equations obtained are a tool for research in trophic ecology, allowing a broader evaluation of the role of the lagoon silverside in the diet of piscivorous predators.